2018
DOI: 10.5001/omj.2018.30
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Bilateral Ovarian Mature Cystic Teratomas with Ovarian Torsion: A Case Report

Abstract: Ovarian tumors are a common form of neoplasm in women. Mature cystic teratoma is the most common type, with a bilateral incidence of 8-15%. However, few cases are reported as bilateral and multiple. A rare case of bilateral multiple dermoid cysts in a 19-year-old female patient presented with abdominal pain of one-day duration. Her medical history was unremarkable. Ultrasonography showed multiple bilateral ovarian cystic masses. The patient underwent laparotomy. The masses were excised while preserving the rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…This term was formulated in 1863 in the first edition of Virchow's book about tumours (8). Teratomas can be divided into two groups: a) mature teratomas, which include dermoid cysts, and are generally benign b) immature teratomas, which can be cancerous (9).…”
Section: Definitions and Classificationmentioning
confidence: 99%
See 2 more Smart Citations
“…This term was formulated in 1863 in the first edition of Virchow's book about tumours (8). Teratomas can be divided into two groups: a) mature teratomas, which include dermoid cysts, and are generally benign b) immature teratomas, which can be cancerous (9).…”
Section: Definitions and Classificationmentioning
confidence: 99%
“…Dermoid cysts are bilateral in 8-15% of cases (18). Sometimes ipsilateral multiple ovarian teratomas can occur (with the incidence of about 9%) (9). Ruchi Rathore et al reviewed different studies and revealed that pathology side in unilateral cases may vary depending on studies (19).…”
Section: Locationmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the authors, the frequency varies between 22% and 50% of benign ovarian tumors during pregnancy [1,4,5]. This tumor most often affects women of child-bearing age [2,6,7].…”
Section: Physiopathologymentioning
confidence: 99%
“…More importantly, 15% of these lesions may lead to the risk of ovarian torsion. [1][2][3] Moreover, ovarian torsion considers about 3% of cases of acute abdominal discomfort that present at emergency departments. 4 Although ovarian torsion during pregnancy or the postpartum period is often confused with other acute abdominal diseases, it should not be missed.…”
Section: Introductionmentioning
confidence: 99%